Penandaan Falerin dengan Iodium-131 dan Uji Biodistribusi pada Mencit yang Diinduksi Inflamasi - WIDYASTUTI WIDJAKSANA; AGUS ARIYANTO; GINA MONDRIDA; ARINA KUSUMAWARDANI; AS' ARI NAWAWI; ABDUL MUTALIB (JURNAL ILMU KEFARMASIAN INDONESIA, 2010)
Phalerin is an active component of mahkota dewa (Phaleria macrocarpa (Scheff) Boerl) proven to have an anti-inflammation effect. The labeling of phalerin with gamma emitting radionuclides was aimed to study its pharmacokinetic behavior and particularly to trace its metabolites. The labeling with 131I was caried out using iodogen as oxidator. Radiolabeled compound was characterized by high performance liquid chromatography (HPLC) using C- 18 column eluted with methanol 70% and detected with UV detector (λ=291 nm) and by thin layer chromatography (TLC) using silica gel strips eluted with chloroform-methanol (9:2), and labeling efficiency was determined using the same TLC system. Purification of radiolabeled product Was carried out using size exclusion chromatography (Sephadex G-25 column) eluted with 0.05 M phosphate buffer pH 7.4. Biodistributions of 131l-phalerin in various organs of normal and inilammation-induced mice were observed at 1, 4, and 24 hours post-intravenous injection. Radiochemical purity of 131l-phalerin was 90.2 ± 2.8% and increased to 96.0 ± 0.4% after purification. Radioactivities in inflamed tissue at 1, 4, and 24 hours post-injection were respectively 1.6 times, 1.4 times, and 1.3 times higher than that in normal tissue, The results showed a significant uptake of radiolabeled phalerin in inflamed tissue.